PENGARUH LEVERAGE, UKURAN PERUSAHAAN DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI STUDI KASUS PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2022 - Hawa, Siti; Parlindungan Dongoran; Tita Safitriawati (Universitas Prof.Hazairin,SH Bengkulu, 2024)
This research aims to determine the effect of leverage, company size and liquidity on company value with dividend policy as a moderating variable. This research uses a quantitative approach with secondary data through company financial reports and public reports on the Indonesia Stock Exchange. The research population consists of mining companies listed on the Indonesia Stock Exchange for 2018-2022 with a total of 47 companies. The number of samples in this research was 19 companies obtained through the purposive sampling method. The analysis method used includes descriptive statistical data analysis, panel data, verification statistics, and moderated regression analysis, using the Eviews 12 analysis tool. The partial research results show that leverage, company size and liquidity variables influence company value. Other results, the results of moderate testing show that dividend policy is unable to moderate the influence of leverage and company size on company value, while dividend policy can moderate the influence of leverage on company value.